Penerapan Teknologi Tepat Guna Mesin Pengaduk Pakan Puyuh dengan Metode Horizontal Screw Rotary System di Desa Kedungrejo Kecamatan Muncar - I Gusti Ngurah Bagus Catrawedarma; Akhmad Afandi; Anis Usfah Prastujati (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Some of the problems with quails are the price of feed, quails die when laying eggs, and mixing feed manually, so that egg sales cannot cover the cost of feed. The solution offered through this service program is to apply a horizontal screw type mixer machine and provide training on optimal feed composition to reduce the number of quail deaths when laying eggs and increase the number of egg production by evenly mixing the feed. The pre-implementation of this service began with a survey to partner locations in Kedungrejo Village, Muncar, Banyuwangi to discuss the problems of partner and their solutions. The application, operational assistance, and maintenance of a 125 kg capacity mixer machine are carried out in the implementation of the service, as well as training in making optimal feed compositions. The uses of this machine slightly reduce the financial benefits, but it is very helpful in terms of energy and time in mixing the feed, so there are more positive sides with the use of this machine.